2017
DOI: 10.1073/pnas.1612980114
|View full text |Cite
|
Sign up to set email alerts
|

DNA–PK facilitates piggyBac transposition by promoting paired-end complex formation

Abstract: The involvement of host factors is critical to our understanding of underlying mechanisms of transposition and the applications of transposon-based technologies. Modified piggyBac (PB) is one of the most potent transposon systems in mammals. However, varying transposition efficiencies of PB among different cell lines have restricted its application. We discovered that the DNA-PK complex facilitates PB transposition by binding to PB transposase (PBase) and promoting paired-end complex formation. Mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“… This figure summarizes the observed effects of PGML KDs on Pgm-mediated IES excision. In line with previously published data ( Dubois et al, 2017 ) and known properties of the T. ni PiggyBac transposase ( Jin et al, 2017 ), the catalytically active form of Pgm is assumed to be a dimer. In the absence of information about the stoichiometry of the complex, one Pgm homodimer (active catalytic site drawn as a star) is represented at each IES boundary, with a large bridging structure formed by all PgmLs.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“… This figure summarizes the observed effects of PGML KDs on Pgm-mediated IES excision. In line with previously published data ( Dubois et al, 2017 ) and known properties of the T. ni PiggyBac transposase ( Jin et al, 2017 ), the catalytically active form of Pgm is assumed to be a dimer. In the absence of information about the stoichiometry of the complex, one Pgm homodimer (active catalytic site drawn as a star) is represented at each IES boundary, with a large bridging structure formed by all PgmLs.…”
Section: Discussionmentioning
confidence: 67%
“…The T. ni PB transposase forms a dimer in solution and probably works as a higher-order oligomer during assembly of the transposition complex ( Jin et al, 2017 ). Previous work in Paramecium established that Pgm multimerizes in cell extracts and several Pgm subunits are required to complete IES excision in vivo ( Dubois et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, because most of~10,000 T. thermophila IESs are located in intergenic or other non-coding regions [45], the pressure for precise excision may not be as strong as for P. tetraurelia IESs. Tpb2 likely interacts with Ku70/Ku80, because this appears to be a general property of PiggyBac transposases, be they domesticated or not (this work and [26,46]), but this interaction would simply direct the loading of Ku onto broken ends once DSBs have been introduced, which would represent a minimal form of coupling. Apart from Tpb2-dependent IESs, 12 intragenic piggyBac-derived IESs were described in T. thermophila [47,48].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…In plasmid vectors, it has been demonstrated that a shorter amount of DNA external to the transposon ITRs leads to more efficient transposition with a variety of transposases, including piggyBac. [42][43][44] However, the effect of this configuration in circular plasmid is to physically bring the ITRs closer together, thereby facilitating paired-end complex formation, the initial step in transposition where the transposase aligns both ends of the transposon. 43 The benefit of this transposon ITR configuration in circular vectors is not applicable to linear vectors, where different factors appear to be important.…”
Section: Discussionmentioning
confidence: 99%